Workability and mechanical properties analysis of hybrid fibers reinforced self-compacting concrete incorporating recycled aggregates based on acoustic emission technique. (May 2023) - Gao, Danying; Ji, Dongdong; Gu, Zhiqiang; Yan, Huanhuan; Zhang, Yu
Abstract: This research focused on maximizing the utilization of recycled aggregates to produce hybrid fibers reinforced self-compacting concrete (SCC) suitable for the majority of construction applications. Hybrid fibers, including milling profiled steel fiber with the volume fraction of 1.0 % and polypropylene fiber with the volume fraction of 0.1%, and mineral admixtures were used to improve the mechanical properties and workability of SCC with recycled aggregates, respectively. The influence of recycled coarse aggregate (RCA) and recycled fine aggregate (RFA) in different replacement ratio combinations (25%-0%, 50%-0%, 75%-0%, 100%-0%, 0%-25%, 0%-50%, 25%-25%) on the workability and mechanical properties of hybrid fibers reinforced recycled aggregates SCC (HFRA-SCC) were studied. The acoustic emission (AE) and digital image correlation (DIC) technique were used to monitor the crack development of HFRA-SCC under compression and splitting tensile loading, respectively. Results showed that both RCA and RFA had negative effects on the workability of HFRA-SCC when their replacement ratio exceeded 25% respectively. The mechanical properties of HFRA-SCC decreased with the increase of recycled aggregates replacement ratio as well, while fibers could compensate the strength loss caused by recycled aggregates and significantly increase the toughness of HFRA-SCC. A larger number of AE activities, as well as a sudden spike in cumulative AE energy, could predict the failure of specimen in advance. According to the analysis to the experimental results of this paper, the maximum replacement ratio of recycled aggregates used in HFRA-SCC was proposed.